2010
DOI: 10.1002/chem.201000726
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Cross‐Coupling Reactions of Organogold(I) Reagents with Organic Electrophiles

Abstract: The palladium-catalyzed cross-coupling reaction of organogold(I) reagents (alkyl, alkenyl, aryl, and alkynyl) with organic electrophiles, such as aryl and alkenyl halides, aryl triflates, benzyl bromide, and benzoyl chloride is reported. The reaction takes place, under palladium catalysis, at room temperature with short reaction times to give the corresponding cross-coupling products in high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 39 publications
4
48
0
1
Order By: Relevance
“…Interestingly, the addition of PdCl 2 (PPh 3 ) 2 (5 mol‐%) to a homogeneous H 2 O/THF (9 mL, 2:1) solution of previously isolated PhAuPPh 3 (110 mol‐%) and 4‐iodotoluene (100 mol‐%), afforded the cross‐coupling product 3a in 91 % yield in 1 h at room temperature (Table 1, Entry 1). This result is identical to that obtained with pure THF as solvent (Table 1, Entry 2)11a and shows the high stability of the organogold(I) phosphane in aqueous media (protodeauration was not detected). It is interesting to note that is not necessary to use degassed solvents and that the reaction can be carried out with water taken directly from the tap.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Interestingly, the addition of PdCl 2 (PPh 3 ) 2 (5 mol‐%) to a homogeneous H 2 O/THF (9 mL, 2:1) solution of previously isolated PhAuPPh 3 (110 mol‐%) and 4‐iodotoluene (100 mol‐%), afforded the cross‐coupling product 3a in 91 % yield in 1 h at room temperature (Table 1, Entry 1). This result is identical to that obtained with pure THF as solvent (Table 1, Entry 2)11a and shows the high stability of the organogold(I) phosphane in aqueous media (protodeauration was not detected). It is interesting to note that is not necessary to use degassed solvents and that the reaction can be carried out with water taken directly from the tap.…”
Section: Resultssupporting
confidence: 86%
“…Interestingly, a similar result was also reported by Gagné for the palladium‐catalyzed cross‐coupling reactions between isolated vinyl‐ or arylgold(I) reagents and tolyl triflate 19. In our previous work,11a we reported that when the organogold reagent was generated in situ, the cross‐coupling reaction between 1a and 9 produced 10a in 93 % yield, which suggests that the lithium chloride generated during the formation of the organogold(I) phosphane could play a crucial role in the coupling. The LiCl effect in palladium‐catalyzed cross‐coupling reactions was discovered by Stille when using organotin reagents,20 and can be attributed to stabilization of the palladium species after the oxidative addition.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…[102] More recently, Sarandeses and co-workers obtained related results. [103,104] In both cases the gold(I) de- Blum and co-workers have modified this reaction towards the very good yield synthesis of functionalized butenolides and isocoumarins, using both metals in catalytic amounts. [105] The authors propose the formation of the allyl oxonium intermediate generated by Au-catalyzed cyclization rearrangement of the starting allenoate.…”
Section: Carboauration Reactions Of Alkynesmentioning
confidence: 99%
“…Reports of at least partial success in interfacing Au- and Pd catalysis in this manner have been published by Blum, 10 Hashmi, 11 Sarkar, 12 and Sestelo. 13 In particular, Blum has reported an impressive example of bimetallic catalysis wherein a gold-vinyl intermediate obtained from an allene activation reaction could be intercepted by an in situ formed palladium π-allyl species to perform a vinyl-allyl coupling that was catalytic in both gold and palladium. 14 We report herein that undesirable redox reactions between Pd(0) and Au( i ) can interfere with the normal operation of several putative catalytic cycles that could couple the reactivity of Au and Pd.…”
mentioning
confidence: 99%